대상체의 하드론-요법 치료 동안 하드론 빔을 모니터링하기 위한 방법 및 시스템 - THERS DOMINIQUE; STUTZMANN JEAN SEBASTIEN (2023)
본 발명은 방사성 의약품으로 표지된 종양 세포를 포함하는 대상체의 하드론-요법 치료 동안에 하드론 빔을 모니터링하는 방법으로서, 하드론 빔이 복수의 이산 하드론 버스트를 포함하고, 상기 방법이, 버스트가 대상체에 충격되는 때에, 콤프턴 망원경에 의해서 대상체의 조직과의 버스트의 하드론의 상호작용에 의해서 생성된 즉발 감마선을 검출하는 단계(111), 상호작용 부피의 이미지를 재구성시키는 단계(112); 버스트가 대상체에 충격되지 않는 때에, 콤프턴 망원경(Compton telescope)에 의해서 방사성 의약품으로 표지된 종양 세포의 위치를 추출하는 단계(121), 종양의 전체 부피의 이미지를 재구성시키는 단계(122); 측정된 상호작용 부피를 종양의 측정된 전체 부피에 대해서 위치시키기 위해서 상호작용 부피의 이미지와 종양의 전체 부피의 이미지를 비교하는 단계(131)를 포함하는, 방법에 관한 것이다. A method for monitoring a hadron beam during hadron-therapy treatment of a subject including tumour cells labelled with a radiopharmaceutical product, in which the hadron beam includes a plurality of discrete hadron bursts, the method including the following steps: when a burst impacts on the subject, detecting the prompt gamma generated by the interaction of the hadrons of the burst with the tissues of the subject using a Compton telescope and reconstructing an image of the interaction volume; when no burst impacts on the subject, extracting the position of the tumour cells labelled with the radiopharmaceutical product using the Compton telescope and reconstructing an image of the total volume of the tumour; comparing the image of the interaction volume and the image of the total volume of the tumour so as to locate the measured interaction volume relative to the measured total volume of the tumour.